Financial transaction taxes and the informational efficiency of financial markets: A structural estimation - Marco Cipriani; Antonio Guarino; Andreas Uthemann (Centre for Microdata Methods and Practice (cemmap), 2019)
We develop a new methodology to estimate the impact of a financial transaction tax (FTT) on informational efficiency, liquidity and volatility. In our sequential trading model there are price elastic noise traders and traders with private information of heterogeneous quality. We estimate the model without a tax and then quantify the effect of an FTT. In our sample, noise traders are price elastic but less so than informed traders. The introduction of an FTT changes the composition of the market, lowering informational efficiency. Even a small, 5 bps, FTT impedes correct price convergence on a sizeable percentage of days.
Keywords: G14; D82; C13; 330; Financial Transaction Tax; Market Microstructure; Structural Estimation